Persembahan Ritual Kaul Melanau Dan Hari Moyang Mah Meri : Manifestasi Kepercayaan Dan Kosmologi - Umar, Kalsum (2018)
This study reveals the manifestations of belief and cosmology amongst the Melanau natives in Mukah, Sarawak and Mah Meri indigenous people in Carey Island, Selangor. The beliefs and cosmological manifestations in the ritual ceremony of Kaul Melanau and Mah Meri Ancestors Day are interpreted in this study from the point of the ritualistic structure of the two ceremonies. The beliefs and cosmology are analysed based on both the similar and different points of view. The traditional society of the Melanau Pagan performs a ritual called Kaul, a prayer to the ‘Ipok’ (Spirits) to thank for the blessings and assistance provided in their life. The Mah Meri indigenous people also call upon their Moyang for the same reason. Coincidentally this study begins with the similarity in their aims. The similar and different values found in both rituals from the point of cosmology and belief manifestations are analysed based on the four elements of fire, water, earth and air. These cosmological elements are manifested in the ritualistic offerings of food, taboos, incantation, Bomoh Poyang and Bapak Kaul, as well as time and space. The above structure is also considered as performing arts which proves and emphasizes that both rituals function not only as beliefs but also as a ceremony. This study undertakes the qualitative approach taking into consideration the primary data derived from structured and semi-structured interviews, participation and observation, assisted by the secondary data. The findings of this study would be helpful to further explore other studies about indigenous communities in Malaysia as an effort to uplift the various cultures and heritages.